Analisis persepsi peternak terhadap kompetensi penyuluh dalam pengembangan usaha peternakan sapi potong Di Kecamatan Bacan Timur Tengah - Dodengo, E S; Lainawa, J; Lenzun, G D; Tumewu, J M (Universitas Sam Ratulangi, 2021)
ANALYSIS OF FARMER'S PERCEPTIONS OF EXTENSION COMPETENCY IN BEEF CATTLE BUSINESS DEVELOPMENT IN BACAN DISTRICT, MIDDLE EAST This research was carried out in the Middle East Bacan District, Bibinoi Village, South Halmahera Regency in August 2019. The purpose of this study was to determine the level of farmers' responses to the competence of extension workers in outreach activities in beef cattle farming. Agricultural extension workers are people who play a role in empowering farmers as the main actors in agricultural development in general so that they are able to develop businesses according to their local capabilities and resources.The type of research used is a qualitative descriptive method with an approach to extension activities carried out to farmers in Bacan Timur Tengah District, South Halmahera Regency with a concentration on Bibinoi Village because this village has farmers who raise cattle. Selection of respondents by taking 30 breeders, variable measurement was carried out by applying a Likert scale whose measurements were scored on each perception. The results showed that the overall perception value of beef cattle breeders on the competence of extension workers in Bibinoi village, Bacan Timur Tengah District, South Halmahera Regency, the most prominent was professional competence and social competence with a percentage of 100%. Overall, the perceptions of beef cattle breeders on the competence of extension workers were seen from the personality competency, 80% rated very like and 13.33% rated like mean while, 6.67% said they didn't like it. Competence, 93.33% rated very like and 6.67% rated like. Professional competence and social competence 100% of breeders rated very like it. Farmers 'perceptions of extension agents' competency showed the results were mostly very like 100% and a small proportion did not like 6.67% technology.